A Pengaruh Model Pembelajaran dan Media Pembelajaran terhadap Keaktifan Belajar Siswa Kelas X SMA Wachid Hasyim 2 Taman Sidoarjo - Nunuk Anggraini; Laila Badriyah; Eli Masnawati (Al-Munawwarah : Jurnal Pendidikan Islam, 2024)
This study aims to determine the effect of learning models and learning media on the learning activity of class X students at SMA Wachid Hasyim 2 Taman Sidoarjo. The author uses a quantitative research type using a quantitative survey approach. The research respondents numbered 153 students. The author uses research data in the form of a questionnaire and analyzed by t-test using SPSS 26 Software. The results of this study indicate that there is an effect of learning models on student learning activity supported by the calculation results, namely the t-count value of 5.658> t table 1.975 and there is an effect of learning media on student learning activity supported by the calculation results, namely the t-count value of 5.350> t table 1.975, This shows that Ho is rejected and Ha is accepted, and it can be concluded that learning models and learning media significantly affect the learning activity of class X students at SMA Wachid Hasyim 2 Taman Sidoarjo. By using various learning models, students can be more actively involved and motivated in the learning process. Educators are advised to utilize interactive and interesting learning media, this can help students understand the material better and increase their participation in learning activities.